The American Convention on Human Rights : crucial rights and their theory and practice / Cecila Medina Quiroga. - Medina Quiroga, Cecilia, 1935- (Intersentia, 2016)
The American Convention on Human Rights contains an in-depth analysis of and comment on crucial rights protected under the American Convention on Human Rights in the light of the decisions of the Inter-American Court of Human Rights. It shows the initially hesitant steps of the Inter-American Court in developing its position on five basic rights in the first years of its existence (1979-2003). Violations of the core rights - namely the right to life, the right to personal freedom, the right to personal integrity, the right to due process of law and the right to a judicial remedy - formed the majority of complaints before the Court at a time when many of the contracting States had either just left, or were still immersed in, a dictatorship and were only just attempting to introduce the idea of human rights in a democratic society into their own legal systems. This fully revised and updated second edition now also covers the Inter-American Court's steps towards maturity (2004-2014). Due to the political and social changes in the region, since 2003 the Court has had to examine and consider a greater variety of rights, such as freedom of speech, structural discrimination, and the lack of proper protection for women's human rights and for people with different sexual orientations. The human rights problems of indigenous peoples have also come to the Court's attention, because the lack of judicial protection of their rights leads to State responsibility by omission. In addition, systematic and gross violations of human rights continue to be a significant part of the Court's work, but their treatment has allowed the Court to develop better and more precise and effective responses.Taking into consideration the changes that have taken place, this book has given more attention to certain topics. A chapter on disappearances is now included. Developments in the way the Court understands its own functions, such as the idea of the State agents' conventionality control, are also discussed.In addition, a new introductory chapter provides a good overview of the social and political landscape of the region and a wider analysis of discrimination and equality.The American Convention on Human Rights is a scholarly yet practical book on a relatively new system for the protection of human rights. It is a useful tool for practitioners to support their work and for academics in their teaching of the inter-American System.